TECPR1 conjugates LC3 to damaged endomembranes upon detection of sphingomyelin exposure - Boyle,KB; Ellison,CJ; Elliott,PR; Schuschnig,M; Grimes,K; Dionne,MS; Sasakawa,C; Munro,S; Martens,S; Randow,F (The EMBO Journal, 2023)
Invasive bacteria enter the cytosol of host cells through initial uptake into bacteriacontaining vacuoles (BCVs) and subsequent rupture of the BCV membrane, thereby exposing to the cytosol intraluminal, otherwise shielded danger signals such as glycans and sphingomyelin. The detection of glycans by galectin8 triggers antibacterial autophagy, but how cells sense and respond to cytosolically exposed sphingomyelin remains unknown. Here, we identify TECPR1 (tectonin betapropeller repeat containing 1) as a receptor for cytosolically exposed sphingomyelin, which recruits ATG5 into an E3 ligase complex that mediates lipid conjugation of LC3 independently of ATG16L1. TECPR1 binds sphingomyelin through its Nterminal DysF domain (N'DysF), a feature not shared by other mammalian DysF domains. Solving the crystal structure of N'DysF, we identified key residues required for the interaction, including a solventexposed tryptophan (W154) essential for binding to sphingomyelinpositive membranes and the conjugation of LC3 to lipids. Specificity of the ATG5/ATG12E3 ligase responsible for the conjugation of LC3 is therefore conferred by interchangeable receptor subunits, that is, the canonical ATG16L1 and the sphingomyelinspecific TECPR1, in an arrangement reminiscent of certain multisubunit ubiquitin E3 ligases.